Decay rate of antiS1/S2 IgG serum levels after 6 months of BNT162b2 vaccination in a cohort of COVID-19-naive and COVID-19-experienced subjects - Borgonovo, Fabio; Stangalini, Carlo Alberto; Tinelli, Carmine; Mariani, Chiara; Mileto, Davide; Cossu, Maria Vittoria; Abbati, Laura; Bilardo, Lara; Gagliardi, Gloria; Cutrera, Miriam; Pellicciotta, Martina; Armiento, Luciana; et al. (Human vaccines & immunotherapeutics, 2022)
Vaccination toward SARS-CoV-2 reduced mortality and 'boosters' are being implemented. We offer scientific contribution about IgG production in the COVID-19 experienced population. From January 2021 to March 2021, 183 residents and staff from the Elderly Nursing Home "San Giuseppe Moscati" who had received two doses of the BNT162b2 vaccine were enrolled. The antibody response was assessed by the DiaSorin LIAISON-CLIA S1/S2® IgG solution. Cutoff levels for response (>39 BAU/mL) and neutralizing activity (>208 BAU/mL) were derived from DiaSorin official data. Serology was assessed before and after the first vaccination, and 2 weeks and 6 months after the second vaccination. Anti-S IgG in COVID-19 experienced, baseline IgG producers spiked after the first vaccination to median 5044 BAU/mL and decayed at 6 months to 2467.4 BAU/mL. Anti-S IgG in COVID-19 experienced, baseline IgG non-producers spiked after the second vaccination to median 1701.7 BAU/mL and decayed at 6 months to 904.8 BAU/mL. Anti-S IgG in COVID-19 naïve subjects spiked after the second vaccination to median 546 BAU/mL and decayed at 6 months to 319.8 BAU/mL. The differences between sequential timepoint levels in each group were statistically significant (p < .0001). Serology analysis revealed different kinetics between COVID-19 experienced subjects depending on baseline response, possibly predicting different IgG persistence in blood.